Usulan keamanan mesin winding horizontal dengan metode Risk Reduction Management: Studi kasus di PT. XYZ - Hendri Hendri (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The purpose of this research is to analyze the current state of the system and facilities, machinery and equipment of horizontal winding machines from the safety, technical and environmental aspects in order to provide proposals for repair or improvement of current conditions and mitigation efforts Risk, especially in the scope of horizontal winding machine at PT XYZ, which is a fabrication company that produces tranformers and electric tranformer care services.  The method of analysis used in this research is Risk Reduction Management (RRM) consisting of two main phases: risk assessment and risk reduction of the security of a machine. Risk assessment involves a risk reduction followed by risk evaluation (risk analysis) and other risks. Based on the risk evaluation can be proposed risk reduction proposal. Based on the RRM analysis is found the potential risk of electrical system potentially occurring short-circuit and potentially uncontrolled mechanical objects, hand-pinned and uncontrollable engine rotation. To make the machine safe, proposed improvements to the electrical system (foot switch cable, cable fireplace, and periodic panel cleaning), as well as smoothing the mechanical system (making warning, inspection, protective fence, protective equipment, and emergency stop). Some of the recommendations can be well implemented by the company.